2020
DOI: 10.1057/s41254-020-00187-y
|View full text |Cite
|
Sign up to set email alerts
|

Rural place branding processes: a meta-synthesis

Abstract: Like cities and nations, rural places have adopted the practice of place branding to improve their reputation and increase their competitiveness to attract residents, tourists, and consumers. This review aims to synthesize case studies of rural place branding in order to identify different types of processes applied and relating them to the contextual factors underlying their application. A typology of five rural place branding processes (PBP) is proposed, based on the existence and dominance of a focal actor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 74 publications
0
29
0
Order By: Relevance
“…In particular, it is an attractive strategy of cooperation for neighbouring countries with a similar history, geography and social ties of the population. The importance of research into competitiveness and the importance of rural areas are also confirmed [22].…”
Section: Introductionmentioning
confidence: 90%
“…In particular, it is an attractive strategy of cooperation for neighbouring countries with a similar history, geography and social ties of the population. The importance of research into competitiveness and the importance of rural areas are also confirmed [22].…”
Section: Introductionmentioning
confidence: 90%
“…Moroz et al (2020) argue that the success of rural branding is determined by the following elements: the integrity of representations about the functions of the brand as a factor in defining new economic relationships; the motives and behaviour of agents in the process of implementing brand projects; comprehensiveness and availability of market information about projects; and the models of decision-making by the agents. Gulisova (2020) states that bottom-up processes in rural branding are more common than in other types of place branding. …”
Section: Place Branding Rural Branding and Agrarian Branding: A Conce...mentioning
confidence: 99%
“…the models of decision-making by the agents. Gulisova (2020) states that bottom-up processes in rural branding are more common than in other types of place branding.…”
Section: Place Branding Rural Branding and Agrarian Branding: A Conce...mentioning
confidence: 99%
“…Based on the perception of place identity as a notion formed through a wide range of interdisciplinary discourse (Govers & Go, 2009), the positioning should be taken as an attempt at its communicative expression (Kavaratzis & Hatch, 2013; Grey & O'Toole, 2020). A similar method was used by Barbora Gulisova (Gulisova, 2021), while noting that the right of initiative and final consent in determining the key characteristics of territory still belong to the population living in this territory and/or its representatives. Based on the literature review, the purpose of this study was defined as the identification of key characteristics used by low-urbanized territories for positioning, with two specific objectives, namely:…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%